My dysphoria blues: Or why I cannot write an autoethnography. Issue 1 (February 2019) - O'Shea, Saoirse Caitlin
In this essay, I would like to ask if we are concerned with writing about difference or writing differently. I attempt to present an account of my on-going experience of dysphoria and consider how I write about that experience. I reveal how my writing has no epiphany, is repetitive and in its characterless depiction of others is a two-dimensional, monologue that fails the conventions of an evocative autoethnographic account. My writing is 'bad writing' but what should become of it? Does a concern with style, whether or not over content, based on taste preclude some stories and different ways of writing? Should I be excluded from academe and silenced, or can room be found for a tasteless account like mine? I end my essay by provocatively owning the label of bad writing.